Influence of the oxygen feed distribution on the performance of a catalytic reactor for ATR of methane - Rodriguez, Maria Laura (2010)
In the present contribution, a theoretical study of a multitubular membrane reactor (MR) for the autothermal reforming of methane (ATR) over a Ni/MgOAl2O3 catalyst is presented. By means of a pseudo-homogeneous 1D model, the viability and convenience of the proposed design to produce hydrogen to feed a PEM fuel cell of 10 kWth is analyzed. The influence of the operating conditions on the reactor behavior is studied. The results suggest that the MR is a promising alternative to conventional reactors to carry out ATR of methane at milder conditions and with similar H2 productions. The axial distribution of the O2 fed to the reactor is a powerful tool to influence the axial temperature profiles, the methane conversion and the selectivity. However, the reactor should be operated carefully, to avoid operating conditions where an accumulation phenomenon of oxygen along the axial axis appears.